Bank Involvement with SMEs : Beyond Relationship Lending - de la Torre, Augusto; Martínez Pería, María Soledad; Schmukler, Sergio L. (World Bank, Washington, DC, 2012)
The "conventional wisdom" in academic and policy circles argues that, while large and foreign banks are generally not interested in serving SMEs, small and niche banks have an advantage in doing so because they can overcome SME opaqueness through relationship lending. This paper shows that there is a gap between this view and what banks actually do. Banks perceive SMEs as a core and strategic business and seem well positioned to expand their links with SMEs. The recent intensification of bank involvement with SMEs in various emerging markets documented in this paper is neither led by small or niche banks nor highly dependent on relationship lending. Rather, all types of banks are catering to SMEs and larger, multiple-service banks have in fact a comparative advantage in offering a wide range of products and services on a large scale, through the use of new technologies, business models, and risk management systems.